2001
DOI: 10.1002/jcc.1159
|View full text |Cite
|
Sign up to set email alerts
|

Combined QM/MM study of the opsin shift in bacteriorhodopsin

Abstract: Combined quantum mechanical and molecular mechanical (QM/MM) calculations and molecular dynamics simulations of bacteriorhodopsin (bR) in the membrane matrix have been carried out to determine the factors that make significant contributions to the opsin shift. We found that both solvation and interactions with the protein significantly shifts the absorption maximum of the retinal protonated Schiff base, but the effects are much more pronounced in polar solvents such as methanol, acetonitrile, and water than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
84
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 77 publications
4
84
0
Order By: Relevance
“…Although a number of QM͞MM studies have been reported (9) for Rh proteins only a few used ab initio QM. Yamada et al (10) …”
Section: Methodsmentioning
confidence: 99%
“…Although a number of QM͞MM studies have been reported (9) for Rh proteins only a few used ab initio QM. Yamada et al (10) …”
Section: Methodsmentioning
confidence: 99%
“…In a similar vein, the use of reference data from experimental spectra measured in solution calls for a treatment of solvent effects, which makes it less straightforward to directly assess the intrinsic quality of the quantum chemical description of an excited state. In this regard, gas-phase data are preferable for benchmarking purposes, despite the many methodological possibilities [8][9][10] to model solvatochromic shifts [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, the isolated (i.e., gas-phase) models 1 and 2 (Scheme 1) are taken as qualitative (first order) models for contact ion pairs of PSB11 and PSBT. In fact, both computational (23)(24)(25)(26) and experimental (27,28) results indicate an Ϸ60°twisted (i.e., quasi-deconjugated) 6-s-cis ␤-ionone ring for retinal chromophores, supporting the use of five conjugated double bond models. ‡ ‡ Furthermore, the small difference between the absorption maxima of PSBT and PSB11 in This paper was submitted directly (Track II) to the PNAS office.…”
mentioning
confidence: 99%